DELINEATION OF ERUPTION PRODUCTS AND GEOTHERMAL PROSPECT ZONES IN MOUNT SLAMET, CENTRAL JAVA USING LANDSAT 8 AND GEOCHEMICAL DATA - Annisa, Hiskia Ulinuha; Prasetya, Yogi Adi; Hadna, Zahra Nuraini; Maghfira, Puspita Dian (JGE (Jurnal Geofisika Eksplorasi), 2025)
Mount Slamet, located in Central Java, Indonesia, is one of the promising geothermal prospect areas due to its active volcanic system and distinct surface manifestations such as hot springs and altered grounds. This study aims to identify potential geothermal zones around Mount Slamet by integrating geochemical analysis and remote sensing data. Geochemical measurements from hot springs show temperatures ranging from 48–89 °C, pH values between 6.2–7.1, and elevated concentrations of SiO₂ (90–145 mg/L) and Cl⁻ (18–42 mg/L), indicating high-temperature fluid interaction. Remote sensing techniques, including thermal anomaly detection and alteration mineral mapping using multispectral and hyperspectral satellite imagery, were employed to delineate surface manifestations and hydrothermal alteration zones. The results indicate that the most prospective geothermal area is located in the southwestern part of Mount Slamet, characterized by strong thermal anomalies and geochemical signatures consistent with a high-enthalpy geothermal system. The integration of these methods provides a comprehensive assessment of geothermal potential, revealing key prospect areas with significant thermal anomalies and geochemical signatures indicative of a high-enthalpy geothermal system. These findings enhance understanding of Mount Slamet’s geothermal potential and offer valuable.